Pembelajaran Berdeferensiasi Kelas Iv Muatan Pelajaran Bahasa Indonesia - Rohwati, Genik (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The Emergency Curriculum shows that using this curriculum can reduce the impact of the pandemic by 73% for literacy and 86% for numeracy. The effectiveness of the Emergency Curriculum increasingly shows that it is important to make curriculum changes more comprehensively. Therefore, the Merdeka Curriculum was prepared as a new curriculum that is more comprehensive than the previous curriculum. The aim of the Merdeka Curriculum is to make schools and local governments have the authority to manage their own education in accordance with the conditions in their respective regions, to form human resources of superior quality and high competitiveness, to prepare the nation to face the global challenges of the 4.0 revolution era, to strengthen character education through profiles. Pancasila students. The implementation of the Merdeka curriculum is also followed by various learning methods and strategies and of course with methods that are also student-centered. One of them is differentiated learning which is one of the efforts by educators to empower students to explore all the potential they have. Differentiated learning is a learning process that pays attention to learning activities so that it can accommodate students according to their needs and learning profiles. According to Bayumi, et al (2021), there are three strategies used in implementing differentiated learning, namely: Differentiation of content, process and product.